Mice lacking synapsin III show abnormalities in explicit memory and conditioned fear - Porton, Barbara (2009)
Synapsin III is a neuron-specific phosphoprotein that plays an important role in synaptic transmission and neural development. While synapsin III is abundant in embryonic brain, expression of the protein in adults is reduced and limited primarily to the hippocampus, olfactory bulb, and cerebral cortex. Given the specificity of synapsin III to these brain areas and because it plays a role in neurogenesis in the dentate gyrus, we investigated whether it may affect learning and memory processes in mice. To address this point, synapsin III knockout mice were examined in a general behavioral screen, several tests to assess learning and memory function, and conditioned fear. Mutant animals displayed no anomalies in sensory and motor function or in anxiety- and depressive-like behaviors. Although mutants showed minor alterations in the Morris water maze, they were deficient in object recognition 24 hr and 10 days after training and in social transmission of food preference at 20 min and 24 hr. Additionally, mutants displayed abnormal responses in contextual and cued fear conditioning when tested 1 or 24 hr after conditioning. The synapsin III knockout mice also showed aberrant responses in fear-potentiated startle. Since synapsin III protein is decreased in schizophrenic brain and because the mutant mice do not harbor obvious anatomical deficits or neurological disorders, these mutants may represent a unique neurodevelopmental model for dissecting the molecular pathways that are related to certain aspects of schizophrenia and related disorders.